PMP PRODUKSI PILIS BANGLE HIGEINEIS PADA BAYI BARU LAHIR DI DESA NAGA TIMBUL KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG TAHUN 2023 - kristina, kristina; Ainun, Kamaliah; Zean, Niasti Lasmy; Agustian, Irwan; Pasaribu, Masdalifah; Lubis, Zulfahri (Universitas Budi Darma, 2024)
Partners in this service activity are the PKK Mother's Group located in Naga Timbul Village, Tanjung Merawa District, Deli Serdang Regency The problem faced by PKK mothers is the difficulty of providing information and changing the behavior of postpartum mothers in the use of pilis bangle in babies in a Heigines manner due to cultural influences whose information has been descended from the time of their ancestors. The use of pilis bangle in newborns still has the understanding that the pilis bangle placed on the baby's forehead must be nailed by the parents or grandmothers because the efficacy of parental saliva contains an inner bond with the baby so that the baby can sleep and sleep soundly. Actually using the mouth can cause nosocomial infections in babies The solution to overcome this problem is that postpartum mothers can make hygienic bangle pilis by grinding and making an extract and then mixed with warm water newly placed on the baby's head so as to reduce the risk of preventing nosocomial infections in babies, This activity can be done by housewives to make hygienic bangle excites and increase family income. by conducting IRT training through PKK mothers' camps and making behavior changes and improving health degrees Another target of this service is that this activity is scientifically published in national journals and international journals The results of the 2018 Deli Serdang district health profile data that postpartum mothers still understand the hereditary culture of using bangle on babies with tradition by mouthing them through the mouth because they do not know the risks that will affect babies, The data obtained with a population of 15,552 people and the location of the health center is quite far around 63 km. This is the main reason for the implementation of PKM which will be carried out in collaboration with health education institutions of the Faculty of Health Sciences, Haji University of North Sumatra and to provide health education information to postpartum mothers in improving health using Bangle plants as an initial preventive and therapeutic measure. To realize this, the method used is to approach the postpartum mother to maintain the health of the baby without the risk of disease or infection due to wrong behavior in providing comfort and treatment to the baby. With this, PKK mothers provide health education about making Higeines bangle pilis which is extracted in its use and increase the income of housewives